Strategi Dalam Mengembangkan Minat dan Bakat Mahasiswa Melalui Analisis SWOT (Studi Kasus: Program Studi Kehutanan Fakultas Pertanian Universitas Mataram) - Nurul Chaerani; Irwan Mahakam Lesmono Aji; Kornelia Webliana; Hasyyati Shabrina; Fauzan Fahrussiam; Andrie Ridzki Prasetyo; Musdi Musdi; Dini Lestari (Sasambo: Jurnal Abdimas (Journal of Community Service), 2023)
Program studi Kehutanan Fakultas Pertanian Universitas Mataram merupakan satu-satunya Prodi Kehutanan Perguruan Tinggi Pemerintah, yang ada di kawasan Bali dan Nusa Tenggara dengan jumlah mahasiswa setiap tahunnya yang terus bertambah. Pertambahan mahasiswa tersebut berbanding terbalik dengan jumlah mahasiswa yang mengikuti kompetisi dan perlombaan di bidang Akademik. Berdasarkan Laporan Kinerja Program Studi (LKPS) Tahun 2020 – 2022 menunjukkan prestasi akademik mahasiswa Prodi Kehutanan masih minim yaitu sekitar 1.3%. Hal tersebut perlu ditindak lanjuti untuk meningkatkan motivasi dalam menunjang minat dan bakat mahasiswa. Pengembangan minat dan bakat dapat diawali dengan melakukan analisis SWOT, sehingga tujuan dari pengabdian ini yaitu mengetahui posisi Prodi Kehutanan dalam menentukan rencana strategi pengembangan minat dan bakat mahasiswa dalam meningkatkan prestasi akademik melalui analisis SWOT. Pengumpulan data menggunakan pendekatan kualitatif dan kemudian dikembangkan kedalam data kuantitatif, dengan mengkaji faktor internal dan eksternal melalui kegiatan Focus Group Discussion (FGD) bersama stakeholder Prodi Kehutanan dan penjamin mutu internal Fakultas sebanyak 21 orang. . Hasil analisis berdasarkan perhitungan IFAS dan EFAS menunjukkan bahwa posisi Prodi Kehutanan berada pada kuadran III dengan titik (x = -0.4) dan (y = 0.07) yang menunjukkan strategi WO (Weakness-Opportunity) yaitu Prodi Kehutanan harus “mengubah strategi” dengan meminimalisir kendala dan kelemahan internal agar dapat meningkatkan prestasi mahasiswa. Strategy To Develop the Interest and Talent of Students Through SWOT Analysis (Case Study: Forestry Study Program the Faculty of Agriculture, University of Mataram)  The forestry study program at the Faculty of Agriculture, University of Mataram is the only forestry study program at a state university in the Bali and Nusa Tenggara region, with an increasing number of students applying each year. However, the increased number of students did not correlate positively with the number of students participating in various academic competitions or events, hence the low achievement recorded. Based on the 2020-2022 Forestry study program performance report, the academic achievement of students in the forestry study program was very low at only 1.3%. This problem needs to be followed up to increase motivation in supporting student interests and talents. The development of interests and talents can be started by conducting a SWOT analysis, so that the purpose of this service is to find out the position of the Forestry Study Program in determining strategic plans for developing student interests and talents in increasing academic achievement through SWOT analysis. Data collection was carried out using a qualitative approach and then developed into quantitative data, by examining internal and external factors through Focus Group Discussion (FGD) activities with Forestry Study Program stakeholders and the Faculty's internal quality assurance. Analysis based on IFAS and EFAS calculations showed that the Forestry study program was located in the 3rd quadrant, with points (x = -0.4) and (y = 0.07) indicating that the Forestry study program should adopt WO strategy (weaknesses-opportunities). This means that the Forestry program needs to change its strategy by minimizing the obstacles and internal weaknesses to take advantage of the opportunities that exist in Order To Upgrade Students’ Capabilities